Stereolithography 3D printing for the investigation of acoustic focusing - Febrinawarta, Burhan; Miasa, I Made; Widyaparaga, Adhika; Sucipto, Sucipto; Premiaji, Witnadi Dardjat (Journal of Engineering and Applied Technology, 2024)
In our environment, acoustic sound waves transform into undesirable noise when their intensity exceeds 100 dB, prompting a need for effective mitigation strategies. In recent years, there has been increasing interest in utilising sound/noise and acoustics for energy harvesting, especially for low-power electronic devices committed to clean renewable energy sources. Metamaterials, with a spotlight on metalens, are emerging as a promising solution for precise sound focusing and energy conservation. This study delves into the intricate process of fabricating metalens through Stereolithography (SLA) 3D printing, unravelling their acoustic focusing capabilities. Metalenses, equipped with intricately designed labyrinthine unit cells tailored for manipulating reflected wave phases, materialize through the precision of SLA 3D printing, forming a sophisticated multilateral structure. The experimental framework for acoustic focusing integrates essential components such as a waveguide, speaker array, metalens, acoustic foam, and a sound level meter. The resultant metalens, composed of 22-unit cells with diverse dimensions, distinctly demonstrate robust acoustic focusing capabilities. Calibration procedures are systematically applied to ensure uniformity of speaker array output and to create a carefully controlled acoustic environment. Sound level measurements clearly depict zones of mutually reinforcing resonance heights, while, conversely, there are also zones of mutually attenuating sound. The complex interplay of sound waves through the metalens, intricately guided by the design of the unit cells, decisively determines the degree of acoustic focus achieved. The SLA 3D printed metalens emerges as a compelling manifestation of effective sound concentration, poised for potential applications in the realm of acoustic energy harvesting. Nevertheless, the study's consequential findings beckon further scientific exploration, prompting an in-depth comprehension of the nuanced impacts of input frequency and potential heating phenomena.